2021
DOI: 10.1039/d0mh01341b
|View full text |Cite
|
Sign up to set email alerts
|

Spinodal-modulated solid solution delivers a strong and ductile refractory high-entropy alloy

Abstract: A combination of high yield strength (1.1 GPa) and large tensile elongation to failure (28%) is achieved in a HfNbTiV refractory high-entropy alloy by creating modulated nanoscale inhomogeneity in both composition and lattice strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A second prominent class of HEA systems are refractory high-entropy alloys (RHEAs), which comprise mostly refractory elements and invariably crystallize as body-centered cubic ( bcc ) solid solutions; these alloys have been considered as promising candidate materials for elevated-temperature applications due to their exceptional resistance to softening and extremely high melting points 9 11 . Although many practical challenges remain in the processing of RHEAs due to their brittleness and oxidation susceptibility 12 , numerous RHEAs have been designed, fabricated, and assessed experimentally, with additional insight coming from computational approaches 13 17 . Specifically, to investigate the deformation of RHEAs, transmission electron microscopy (TEM) studies on RHEAs have shown a dominant role of screw dislocations with increasing plastic strain 18 , 19 , and slip activity on high-order-planes has been observed through in situ scanning electron microscopy experiments 16 ; indeed, strong intrinsic lattice resistance has been generally found in these concentrated solid-solution alloys 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A second prominent class of HEA systems are refractory high-entropy alloys (RHEAs), which comprise mostly refractory elements and invariably crystallize as body-centered cubic ( bcc ) solid solutions; these alloys have been considered as promising candidate materials for elevated-temperature applications due to their exceptional resistance to softening and extremely high melting points 9 11 . Although many practical challenges remain in the processing of RHEAs due to their brittleness and oxidation susceptibility 12 , numerous RHEAs have been designed, fabricated, and assessed experimentally, with additional insight coming from computational approaches 13 17 . Specifically, to investigate the deformation of RHEAs, transmission electron microscopy (TEM) studies on RHEAs have shown a dominant role of screw dislocations with increasing plastic strain 18 , 19 , and slip activity on high-order-planes has been observed through in situ scanning electron microscopy experiments 16 ; indeed, strong intrinsic lattice resistance has been generally found in these concentrated solid-solution alloys 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of high strength and ductility in materials is achieved though the interplay of spinodal decomposition induced periodic compositional fluctuations, elastic strain, and diffusive phase boundaries. An et al observed that compositional fluctuations induced by spinodal decomposition in HfNbTiV RHEA impede dislocation motion, 46 leading to the formation of dislocation walls and entanglement through alternate pathways like cross-slip. This results in a material with a high yield strength (1.1 GPa) and large ductility (28%).…”
Section: Bulk Nanostructured Heasmentioning
confidence: 99%
“…Among various AM technologies, laser directed energy deposition (LDED) and laser powder bed fusion (LPBF) are the most commonly used methods for fabricating HEAs . This thermal history presents opportunities for AM-fabricated HEAs to achieve distinct nanostructures, including dispersed nanoparticles, nanoprecipitates and other exceptional phase structures. …”
Section: Bulk Nanostructured Heasmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a more effective method to increase heterogeneity starting from a MEPA solid solution would be phase separation, i.e., decomposition that involves nucleation-growth and/or spinodal decomposition. [25][26][27][28] From the perspective of free energy, the nucleation-growth mode requires the overcoming of a nucleation energy barrier. The spinodal decomposition is different, where small perturbations can lead to a decrease in free energy: once initiated, the free energy decreases as the compositional difference between the two phases increases, resulting in spontaneous uphill diffusion.…”
Section: Introductionmentioning
confidence: 99%